PENGARUH MEDIA DIORAMA BERBASIS KINCIR AIR TERHADAP MINAT BELAJAR MATERI KOMPONEN EKOSISTEM PADA PEMBELAJARAN IPA KELAS V SEKOLAH DASAR - Mohamad Yahya; Dya Ayu Agustina Putri; Leny Suryaning Astutik (Universitas Negeri Surabaya, 2025)
This study aims to evaluate the impact of the use of learning media in grade V at SDN 1 Panggungrejo and SDN 3 Mojosari. After conducting a survey, the author identified problems, such as the lack of optimal use of learning media by teachers, which resulted in students paying less attention to teachers when delivering material during the learning process in the classroom. To overcome this problem, the researcher provided waterwheel-based diorama media to evaluate whether its use had an impact or not. The method used in this study was quantitative with a quasi-experimental research model in the form of multiple-choice questions. The instruments, in the form of pre-tests and post-tests, were administered in the control class and the experimental class to test students' understanding, and an analysis was conducted to calculate the t-test. The results showed that the experimental class, which used waterwheel-based diorama media, had an effect on students' understanding of the IPAS subject matter on ecosystems. This was in accordance with the calculations made using JAMOVI 2.3.28. A P value of 0.667 was obtained. Because the p value > 0.05, Ho is accepted, so it can be said that there was no effect on the conceptual understanding of elementary school students in the experimental class compared to the control class when the pretest was conducted. Meanwhile, when the posttest was conducted in the control and experimental classes, a p-value < 0.001 was obtained, which means it is less than or lower than (< 0.05). The p-value is < 0.05, so Ho is rejected, and it can be concluded that Ha is accepted. Thus, there is a significant effect on the concept comprehension test between students who participated in learning using waterwheel-based diorama media and students who participated in learning without using waterwheel-based diorama media. Ha: μ1 ≠ μ2. In conclusion, the application of waterwheel-based diorama learning media has a significant effect on fifth-grade elementary school students' understanding of ecosystem material.